Rekonstruksi Pembiyaan UMKM Melalui Dana Umat - Sriyono Sriyono; Faizal Ridwan Zamzany (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The purpose of this research is to provide alternative financing of Small Medium of enterprises through funds people. Funds derived people are managed funds by financial institutions that hold the funds, these funds are derived from the zakat, sodakhoh and infac (ZIS). The techniques used to collect data in this research is the observation, in-depth interviews, documentation on Key Informant. Test the validity of the data using the test of Credibility and Transferability. Testing/verification conclusion withdrawals described with interactive analysis models. The results of his research is the grant Funds provided to the ZIS community gathering together the Funds obtained from the ZIS are conditional. The granting of which are regular given to those who are entitled to receive it in accordance with Islamic law and is usually an consumerist, but nevertheless in the changing times the grant funds also given for financing UMKM